A MIXING PROBLEM FOR A QUASI LINEAR EQUATION WITH PARTICULAR DERIVATIVES WITH SOME LATE ARGUMENT - A. Kalandarov; M. M. Anorbayev; I. J. Jangibayev (American Journals, 2024)
In the work, the solutions of the mixed problem set for the quasi – linear partial differential equation with some delayed arguments were studied, and algorithm for finding its numerical solutions was solved by the finite difference method.
Keywords: mixed problem, delayed argument, quasi linear, numerical solutions, algorithm, finite diffence method, transporent and non revealing schemes, driving.